Chiral structural color from microdomes - Xintao Lai; Tongyu Li; Xiaoyu Hou; Florian Vogelbacher; Jiajun Wang; Yanlin Song; Lei Shi; Mingzhu Li (Proceedings of the National Academy of Sciences, 2025)
Artificial chiral-structural-color materials can carry high-dimensional information based on multiple optical degrees of freedom, providing possibilities for advanced optical security and information storage. However, current artificial chiral-structural-color materials are hindered by their specific compositions, fine nanostructures, and single polarization modulation. Here, we found that microdomes made from common polymers have chiral structural colors with broadband tunability and multiple polarization-modulated chirality. The microdome patterns are easily fabricated by ordinary printing techniques and have inhomogeneous spatial distributions of full polarization states and customizable colors. Our chiral-structural-color microdomes (CSCMs) provide a promising roadmap for high-capacity information encryption and high-security anti-counterfeiting. We developed multidimensional tunable structural color displays and achieved encryption with high information capacity. To further highlight the application potential, we constructed contact lenses integrated with CSCMs for identity authentication with 2 32 distinctive cryptograms.